On rear true bugs (Heteroptera) of Siberia and the South of Russian Far East - N. N. Vinokurov (Acta Biologica Sibirica, 2019)
The annotated list contains information on the distribution of 43 rare species from 11 families of true bugs in Eastern Siberia and the Russian Far East. Of these for the first time is recorded for the Altai Republic Plinthisus vestitus Jakovlev, 1889, Novosibirsk District – Stygnocoris cimbricus (Gredler, 1870), Krasnoyarsk Territory – Megalonotus antennatus (Schilling, 1929) and Yakutia – Salda muelleri (Gmelin, 1790), Microvelia reticulata (Burmeister, 1835), Aradus betulinus Fallén, 1829, Megalonotus chiragra (Fabricius, 1794), Nemocoris falleni R.F. Sahlberg, 1848, Graphosoma lineatum (Linnaeus, 1758). Plant bug Leptopterna dolabrata (Linnaeus, 1758) is recorded for the Primorsky Territory as introduced pest of cereals and perennial grasses.